2018
DOI: 10.1186/s40645-018-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

Maritime continent coastlines controlling Earth’s climate

Abstract: During the Monsoon Asian Hydro−Atmosphere Scientific Research and Prediction Initiative (MAHASRI; 2006-16), we carried out two projects over the Indonesian maritime continent (IMC), constructing the Hydrometeorological Array for Intraseasonal Variation−Monsoon Automonitoring (HARIMAU; 2005-10) radar network and setting up a prototype institute for climate studies, the Maritime Continent Center of Excellence (MCCOE; 2009-14). Here, we review the climatological features of the world's largest "regional" rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 150 publications
(285 reference statements)
1
69
0
1
Order By: Relevance
“…Mori et al (2004) further demonstrated the existence of diurnally migrating convective clouds along the coastal areas of Sumatra. This diurnal precipitation contributes to the climatological heavy rain near the coastline (e.g., Bergeman et al 2015;Ogino et al 2016;Ogino et al 2017;Yamanaka et al 2018). However, these features are still poorly reproduced by numerical simulations, especially in global circulation models with coarse horizontal resolutions (e.g., Sato et al 2009;Love et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mori et al (2004) further demonstrated the existence of diurnally migrating convective clouds along the coastal areas of Sumatra. This diurnal precipitation contributes to the climatological heavy rain near the coastline (e.g., Bergeman et al 2015;Ogino et al 2016;Ogino et al 2017;Yamanaka et al 2018). However, these features are still poorly reproduced by numerical simulations, especially in global circulation models with coarse horizontal resolutions (e.g., Sato et al 2009;Love et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To tackle these questions, we conducted an intensive field campaign named HARIMAU2010 in which we deployed a sounding network and a C-band radar around Jakarta to capture the detailed spatiotemporal variations of the atmospheric states and precipitation features for approximately 1 month (January-February 2010; for additional details, please see Mori et al 2018 andYamanaka et al 2018). Utilizing the obtained sounding data, including the first-ever 2-week-long 8 times/day networked soundings over the MC, the present study aims to estimate the heat and moisture budgets and to combine these results with the radar-derived precipitation morphology to reveal the thermodynamic impacts of the diurnal cycle.…”
Section: Introductionmentioning
confidence: 99%
“…may help in forecasting the onset and duration of the dry season over the Maritime Continent. Consequently, forecasting TC activity can help improve, at least partially, the forecasts for all of the processes associated with the Maritime Continent circulation (55)(56)(57)(58)(59)(60).…”
Section: Implications For the Forecast Of The Dry Season Onsetmentioning
confidence: 99%
“…Many studies have been carried out in the northern part of the Indian Ocean basin (Dey et al, 2015), in particular to study the Indian monsoon (Rajeevan et al, 2013;Das et al, 2017). The northeastern Indian Ocean is well documented due to the presence of the Maritime Continent (Yamanaka et al, 2018) and to the strong influence of the Madden-Julian Oscillation (Riley et al, 2011;Sakaeda et al, 2017;Hung and Sui, 2018). However, it is important to consider the ocean as a whole as it is rather in the southern part of the basin that the positioning of the Mascarene High will partly drive the SIOD (Terray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%